Agrarian conflict and split recognition: The middle way for recognition of the Mapur Bangka Tribe in Indonesia - Iskandar Zulkarnain; Jamilah Cholillah (Faculty of Social and Political Science, Universitas Airlangga, 2023)
Since the New Order regime, access to tin mines has been a disaster for the Mapur Tribe. The desire to live in prosperity from tin mining led to a prolonged structural agrarian conflict and problems of political recognition. This study aims to analyze agrarian conflicts and the recognition debates that surround them and analyze the visibility of discourses on the recognition that is adaptive to the interests of indigenous peoples. Through qualitative research with case studies, this study found that structural agrarian conflict gave rise to social rupture and acts of mutual exclusion between groups. The counter-movement can unite the group and continue the resistance. After the agrarian conflict, indigenous peoples were faced with debates about the legal product of recognition through sectoral laws which gave rise to different interpretations at the Regional Apparatus Organization (OPD) level. This condition gave rise to the phenomenon of split recognition, due to the lack of political will to include the agenda for recognition of Indigenous Peoples (MHA) in regional planning policies. A comprehensive law with a general function is needed as a middle ground for the unification of arrangements regarding MHA.